Bit-interleaved coded modulation : fundamentals, analysis, and design - Szczecinski, Leszek; Alvarado, Alex (John Wiley & Sons Inc., 2015)
Presenting a thorough overview of bit-interleaved coded modulation (BICM), this book introduces the tools for the analysis and design of BICM transceivers. It explains in details the functioning principles of BICM and proposes a refined probabilistic modeling of the reliability metrics-the so-called L-values-which are at the core of the BICM receivers. Alternatives for transceiver design based on these models are then studied. Providing new insights into the analysis of BICM, this book is unique in its approach, providing a general framework for analysis and design, focusing on communicati.